POLISH TOURIST ENTERPRISES ACTIVITY WITHIN THE EUROPEAN UNION - Stefan Bosiacki; Joanna Śniadek (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents the results of research conducted in May 2010 among 110 tourist enterprises operating in Wielkopolska Region. The aim of research was to determine the attitude of Polish tourist entrepreneurs towards the European Union and its projects and to show the changes in their ways of business activities after access of Poland to the EU. Also, the authors of the article emphasize the necessity of appropriate tourism policy conducted by central and local governments.